Polymer nanocomposites - Mai, Y. W., 1946-; Yu, Zhong-Zhen (CRC Press ; Woodhead, 2006)
Polymer nanocomposites are polymer matrices reinforced with nano-scale fillers. This new class of composite materials has shown enhanced optical, electrical and dielectric properties. This important book begins by examining the characteristics of the main types of polymer nanocomposites and then reviews their diverse applications. Part one focuses on polymer/nanoparticle composites, their synthesis, optical properties and electrical conductivity. Part two describes the electrical, dielectric and thermal behaviour of polymer/nanoplatelet composites, whilst polymer/nanotube composites are the subject of Part three. The processing and industrial applications of these nanocomposite materials are discussed in Part four, including uses in fuel cells, bioimaging and sensors as well as the manufacture and applications of electrospun polymer nanocomposite fibers, nanostructured transition metal oxides, clay nanofiller/epoxy nanocomposites, hybrid epoxy-silica-rubber nanocomposites and other rubber-based nanocomposites. Polymer nanocomposites: physical properties and applications is a valuable reference tool for both the research community and industry professionals wanting to learn about these materials and their applications in such areas as fuel cell, sensor and biomedical technology. Gives a comprehensive review of polymer nanocomposites and their propertiesA standard reference on this areaWritten by distinguished editors and a international team of authors.
"Woodhead Publishing and Maney Publishing on behalf of the Institute of Materials, Minerals & Mining."
Keywords: Polymeric composites.; Nanostructured materials.; elektronické knihy; electronic books